Who sold you this, then ? (London : Video Arts, 1973)
The video features the vital importance to ongoing sales, service engineers are often untrained in their critical role of customer relations and sales. It also has relevance in helping sales staff to understand what their back up team has to deal with
Keywords: Marketing; Marketing management